Proposed Performance Management System Design For Courier and Logistics Provider Using Balanced - Fortranansi Firdaus, Devin; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2016)
Abstract. Logistics business in Indonesia has grown rapidly in recent years. Factors causing the growth of the logistics are the business globalization, domestic consumption, economic growth and the increasing of domestic and international commerce (the demand of AEC by the end of 2015). As the biggest courier and logistics services providers in Indonesia, PT.EG Express requires strategy that can help companies to take advantage of opportunity and also maintain customer satisfaction because the competitiveness among similar companies becomes greater as well. Â The purpose of this study was to suggest performance management system design based on the Balanced Scorecard as a request of the company and also prepare the company to become an IPO company. Balanced Scorecard method chosen as a performance management system because this method has been known by all employees of the other methods, so that this method will be easier to be implemented. The methodology used to solve problems that occur is by way of interviews and focus groups discussion (FGD) with the parties concerned. Based on the high level of business competition and the company's internal conditions, it is proposed that the right strategy for the company's business is differentiation focus because the strategy focuses on consumers who will be targeted and in it is in accordance with the company's mission. There is a change in the vision of PT.EG Express to "To be the advance ASEAN supply chain company" as well as with the company's mission to become "To provide the best experience to customers consistently by offering excellence quality services". The core value of the company increased to five values: honesty, discipline, responsibility, visionary and cooperation. Company performance indicators designed based on four perspectives the financial, customer, internal processes, learning and growth perspectives. To ensure all the perspectives go as expected, PT.EG Express using the strategy map and initiatives strategy so that the level of achievement in reviewing the company can be repeated. The result of this research is a guide for PT.EG Express to implement the Balanced Scorecard as Performance Management System. This guide consists of a timeline schedule that starts from the beginning of 2016 and will be implemented at the beginning of 2017, the main resources requirement are software BSC and commitment from all employees, and budgeting estimation plan for as much as Rp 2.870.000.000,-.Â Keywords: Performance Management System, Balanced Scorecard, E-commerce logistic provider services.